2017
DOI: 10.3389/fpsyg.2017.01784
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Consequences of Poverty on Economic Decision-Making: A Hypothesized Model of a Cognitive Mechanism

Abstract: This review focuses on the issue of poverty affecting economic decision-making. By critically evaluating existing studies, the authors propose a structural model detailing the cognitive mechanism involved in how poverty negatively impacts economic decision-making, and explores evidence supporting the basis for the formation of this model. The suggested mechanism consists of a relationship between poverty and four other factors: (1) cognitive load (e.g., experiencing negative affect and stress); (2) executive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 133 publications
1
51
0
6
Order By: Relevance
“…Building upon the aforementioned discussion of education, other examples of discounting in the White poor and working class abound, including forgoing preventative health care, valuing higher pay over benefits or potential advancement, and spending versus savings/investments (see Adamkovič & Martončik, for review). In an eloquent example of this, Mani, Mullainathan, Shafir, and Zhao () demonstrated that White Indiana sugarcane farmers had faster response times and more errors in the context of an experimental task before the harvest (i.e., in the context of scarcity) versus after the harvest.…”
Section: Attitudes Behaviors and Values Of White Poor And Working‐cmentioning
confidence: 99%
“…Building upon the aforementioned discussion of education, other examples of discounting in the White poor and working class abound, including forgoing preventative health care, valuing higher pay over benefits or potential advancement, and spending versus savings/investments (see Adamkovič & Martončik, for review). In an eloquent example of this, Mani, Mullainathan, Shafir, and Zhao () demonstrated that White Indiana sugarcane farmers had faster response times and more errors in the context of an experimental task before the harvest (i.e., in the context of scarcity) versus after the harvest.…”
Section: Attitudes Behaviors and Values Of White Poor And Working‐cmentioning
confidence: 99%
“…Haushofer and Fehr (2014) emphasized the need to study factors potentially contributing to poverty perpetuation. Adamkovič and Martončik (2017) have proposed a theoretical model of a cognitive mechanism describing how poverty affect one`s economic preferences via a cognitive mechanism. Based on the data from 3 studies, we conclude that the model has been falsified, and therefore, the hypothesized mechanism does not explain why a person traps herself in the poverty cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In short, the model by Adamkovič and Martončik (2017) depicts that poverty creates cognitive load in the form of experiencing negative affect and stress. The cognitive load, not poverty per se, impairs one`s executive functions, namely, attention focus, working memory and selfcontrol capacity.…”
Section: The Model and Its Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…This manifests amongst poor renters not only in their daily budgetary decisions, but in their search for housing, which is often short and unsystematic; this is particularly true following eviction, an emergency scenario in which households must quickly secure new accommodation or risk homelessness (Skobba & Goetz, 2013). This can result in low-income individuals signing leases that are no more affordable than their previous ones, but offer short-term benefits, such as more rooms, restarting the cycle (Adamkovi & Martonik, 2017;Desmond, 2016). Cumulatively, these factors increase the probability of an eviction, and hinder the chance of poor families escaping poverty.…”
Section: Persistent Economic Disadvantagementioning
confidence: 99%